COVID-19 Issues in Long-Term Care in Ontario: A Document Analysis - David Oldenburger, Andrea Baumann, Mary Crea-Arsenio, Raisa Deber and Vishwanath Baba (Healthcare Policy, 2022)
The COVID-19 crisis in long-term care in Canada has been characterized as a crisis upon a crisis. This study examines recent documents on the crisis in long-term care in Ontario, using document and thematic analysis to synthesize issues and recommendations from the perspectives of different groups and organizations. Thirty-three documents from 20 organizations were analysed and six thematic areas were identified: resident care; human resources; governance, leadership and management; financing; physical infrastructure and supplies; and training and preparation. The six common themes, as perceived by different perspectives, can inform policy makers on long-term care issues.
Keywords: COVID-19, document analysis, healthcare policy, long-term care, Ontario